Excitation Energy Transfer in meta‐Substituted Phenylacetylene Multibranched Chromophores. Issue 19 (7th June 2016) - He, Guiying; Yu, Chenmin; Li, Yang; Hu, Jiangpu; Liu, Zitong; Zhang, Deqing; Guo, Qianjin; Xia, Andong
Abstract: A comprehensive investigation into the spectral properties and excitation energy transfer in di‐ or tribranched dithienyldiketopyrrolopyrrole (DPP) molecules with meta ‐substituted benzene as a central core (TADPP2‐TT andTADPP3 ), by means of steady‐state and transient measurements and quantum chemical calculations, is reported. Excitation in the meta ‐substituted chromophores is localized on one of the DPP units in the branching molecules owing to the disruption of conjugation by meta substitution for bothTADPP2‐TT andTADPP3 . Weak electronic couplings result from the long distance between the DPP chromophores and the steric effects from the attached side chains on DPP. The attachment of the acetylene linker in each branch, which has a very low twisting barrier, could also play an important role in reducing the interaction between DPP chromophores. The dynamics of the excited states show that excitation energy transfer occurs on the picosecond scale, which is attributed to the incoherent hopping mechanism. Abstract : Branch effects : A comprehensive investigation into the spectral properties and excitation energy transfer in di‐ or tribranched dithienyldiketopyrrolopyrrole molecules with meta ‐substituted benzene as a central core, by means of steady‐state and transient measurements and quantum chemical calculations, is reported (see figure).